Comparative analysis of molecular and physiological traits between perennial Arabis alpina Pajares and annual Arabidopsis thaliana Sy-0. Issue 1 (December 2017) - Park, Jong-Yoon; Kim, Hoyeun; Lee, Ilha
Abstract Annual plants complete life cycle in a year while perennial plants maintain growth for several years.Arabis alpina, a polycarpic perennial, is a close relative of monocarpic annual Arabidopsis. Pajares is an accession ofA .alpina requiring vernalization, a long-term cold for flowering. Arabidopsis shows holistic flowering whereas Pajares shows idiographic flowering, producing axillary branches under variable developmental phases from juvenile, adult vegetative to reproductive phases. To understand the molecular mechanism behind diverse phases of axillary branches, we analyzed the levels of primary miR156 expressions because miR156-SPL module is a key regulator for developmental phase transition. We found that in Pajares, miR156 levels were highly variable among the axillary branches, which causes differential sensitivity to vernalization. Thus, the axillary branches expressing high levels of miR156 remain in juvenile phase even after vernalization, whereas the axillary branches expressing low levels of miR156 produce flowers after vernalization. In contrast, every axillary branches of Arabidopsis winter annual Sy-0 expressed similar levels of miR156 and synchronously responded to vernalization, which causes holistic flowering. Therefore, we suggest that variable miR156 expression levels and the resulting differential response to vernalization among axillary branches are distinctive features determining polycarpic perenniality ofA .alpina Pajares.